Evaluation of a school-based tobacco control intervention in India. (November 2020) - Lakshmi, Josyula K; Shrivastav, Radhika; Saluja, Kiran; Arora, Monika
Objective: To understand tobacco use patterns and the context, implementation and reception of a 2-year school-based behavioural intervention to promote awareness and support for tobacco control policies. Design: Qualitative exploration of participating students', parents' and teachers' perspectives, experiences and observations related to tobacco use and the school-based intervention, as well as suggestions for the more effective prevention of tobacco use. Setting: 1, 440 schools (720 intervention, 720 control) in two districts of Andhra Pradesh and five districts of Gujarat, India, participated in the study. Method: Forty-six focus group discussions were conducted with 94 teachers, 105 parents and 138 students in the intervention schools. Results: Evaluation findings signal the influence of the social, economic and cultural context on the initiation and perpetuation of tobacco use. Positive health beliefs, the economic importance of tobacco and cultural practices related to tobacco use were at variance with mounting evidence on the adverse outcomes of tobacco use. Health behaviour change related to tobacco use was observed in participating students, teachers and their families. However, the wider community was not as much influenced. Analysis of the intervention revealed various inputs and gaps in the implementation of the intervention associated with low impact on tobacco use in the community. Conclusion: School-based interventions can effect significant perceived health behaviour change among students and families. Health promotion interventions need to acknowledge, harness and address cultural norms, economic pressures and policy implementation with respect to the initiation and perpetuation of tobacco use health behaviours.